2003
DOI: 10.1542/peds.111.2.e120
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Communication Practices Between State Newborn Screening Programs and the Medical Home

Abstract: ABSTRACT. Background. As outlined in the Newborn Screening Task Force report published in August 2000, the newborn screening system is more than just testing, but also involves follow-up, diagnosis, treatment, and evaluation. As such, multiple professional and public partners need to be adequately involved in the system to help ensure success. In addition, newborn screening programs are state-based; therefore, policies and procedures vary from state to state. Historically, there has been little uniformity betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 6 publications
1
44
0
1
Order By: Relevance
“…In addition, few data exist on the knowledge and needs of parents and health care professionals for education in this area. 1,2 The American Academy of Pediatrics (AAP) Newborn Screening Task Force recommended in 1999 that each state design and implement parent education efforts regarding newborn screening. 2 Although written educational materials regarding newborn screening now exist in 49 of the 51 US states/territories, their effectiveness may be hampered by dissemination problems and lack of reading ease.…”
mentioning
confidence: 99%
“…In addition, few data exist on the knowledge and needs of parents and health care professionals for education in this area. 1,2 The American Academy of Pediatrics (AAP) Newborn Screening Task Force recommended in 1999 that each state design and implement parent education efforts regarding newborn screening. 2 Although written educational materials regarding newborn screening now exist in 49 of the 51 US states/territories, their effectiveness may be hampered by dissemination problems and lack of reading ease.…”
mentioning
confidence: 99%
“…Neonatal screening is a system of five stages that is habitually organized and carried out by the public health system, which has the resources and authority necessary to carry out universal screening, and in which pediatricians play an important role. 2,13,14,17,[19][20][21] The first step is to carry out the screening tests themselves. The objective is to achieve universal screening, i.e., all newborn infants should be screened.…”
Section: The Concept Of Neonatal Screeningmentioning
confidence: 99%
“…13,14,22,23 The Newborn Screening Expert Group found a clear disparity between the information available and the information needed by the primary care physician (pediatricians and family doctors) to ensure an immediate response to positive screening tests and so recommended that professional training should be the responsibility of the screening system. They also developed a list of actions (ACT sheets) to be taken in the event of a positive diagnosis for each of the diseases proposed for testing.…”
Section: Physicians' Knowledge About Expanded Screening By Tandem Masmentioning
confidence: 99%
See 1 more Smart Citation
“…Because many parents are informed about newborn screening just before specimen collection, it is essential that all clinicians involved in the health supervision of newborns and expectant mothers be well informed about genetics and specifically about newborn screening. A survey by Kim et al 5 indicated that the techniques used most commonly to inform and to educate parents were informational brochures and a conversation with the parents (generally the mother of the newborn) immediately before or after the birth of the infant. The survey found, however, that states seldom defined who would have the role of and responsibility for informing and educating parents about newborn screening.…”
Section: Promoting Education and Training For Families And Health Carmentioning
confidence: 99%